Relationship between nurse's performance and responsibilities with the patient's pickup time in the recovery room - Arief Yanto (Media Keperawatan Indonesia, 2020)
Hospital services are one of the management of post-surgical patients which is supported by the performance of nurses in nursing services who are responsible for post-surgical patients. Preliminary survey data on 100 postoperative patients, the average pick-up by room nurses so that the purpose of this study was to determine the relationship between nurse performance and responsibility and patient pick-up time in the recovery room. The design used in this research is associative quantitative research, with a cross-sectional approach. Subjects that have been studied were 41 nurses, which were obtained through simple random sampling. Measuring tools that have been used in this study are questionnaires and observation sheets. The results of this study indicate that the performance of nurses in the good category is 61%, and 39% poor performance. The responsibility of the nurse in the good category is 58.5%, and the less responsibility is 41.5%. The time for picking up patients in the IBS Room by nurses with fast time was 53.7% and less fast 46.3% of nurses. There is a relationship between the nurse's performance and the time to pick up patients in the recovery room (p-value = 0.048) and there is a relationship between the responsibilities of nurses and the time to pick up patients in the recovery room (p-value = 0.003). The hospital is improving nursing services by increasing the ability of nurse resources through continuous monitoring according to hospital service standards.